Загрязнения теплопередающей поверхности теплообменных аппаратов с интенсификацией теплоотдачи - Арсеньева, Ольга Петровна; Янг, М.; Критенден, Б.; Капустенко, Пётр Алексеевич (НТУ "ХПИ", 2012)
The processes of fouling formation for cooling water side in plate heat exchangers are investigated. The mathematical model, which is capable to predict fouling thermal resistance for precipitation and particulate fouling at different flow velocities and surface temperatures, is developed. This model can be used for plate heat exchangers with enhanced heat transfer and also for straight channels with heat transfer intensification. On initial stage of fouling formation it can be described by “threshold model” proposed for bare tubes and tubes with enhanced heat transfer by Yang and Crittenden. For correct predictions of fouling thermal resistance by this model it is necessary to determine experimentally one model parameter for given cooling water fouling properties.
Keywords: загрязнение; охлаждающая вода; отложения; теплообменники пластинчатые; накипь; математическая модель; термическое сопротивление; теплоотдача